Assessing the anthropogenic threats to vultures in the communal farmlands of Namibia - Craig, Christie (Percy FitzPatrick Institute of African Ornithology, 2017)
The use of poison by farmers to control livestock predators is a major threat to vulture populations across Africa. In Namibia, there is now some understanding of poison use on commercial farms, but the situation in the communal farmlands is still poorly understood. Using a series of 36 questions, I interviewed 367 communal farmers to assess the prevalence of poison use across the north-west, north and eastern communal land. I found that 18% (SE 2.8) of farmers had killed a predator in the last year and 1.7% (SE 2.1) used poison to do so. I mapped the probability of poison use across the communal regions surveyed and found that poison use is predicted to be higher (up to 7% of farmers using poison) in some areas of the upper north-west. In contrast to previous research, those living adjacent to protected areas did not experience greater losses to predators and as a result were not more inclined to use poison. I found that those using poison are more likely to own greater numbers of livestock, particularly large livestock. Overall, my study suggests that poison use is approximately 12 times lower in the communal areas than on commercial farms. A number of farmers expressed that it is dangerous to use poison on communal land as the risk of non-target impacts is much higher where the land is not fenced and is communally used. Nonetheless there are communal farmers who are using poison and this poses a risk to already threatened vulture populations. Lastly, I did a survey to look at the farmers' local knowledge about vultures, their attitudes towards them and any cultural value that vultures hold. Overall vultures were viewed positively by farmers. The cultural use of vulture parts appeared fairly uncommon, with 9.5% of farmers reporting that they knew of uses. Many farmers indicated that the cultural use of vulture parts was something practiced by previous generations. Feathers were the most commonly used part, mainly for decorations and making arrows. From my assessment, it appears that anthropogenic threats to vultures in communal areas are fairly low. The cultural use of vulture body parts is rare. In addition, poison is used but this practice is not nearly as common as it is on commercial farms. Since poison can have such devastating impacts on vulture populations, I nonetheless advise that reactive and preventative measures are put in place to reduce poisoning and minimise the impact when poison is used. The identified 'hotspots' of poison use will assist local authorities to focus their poison mitigation efforts.